Large multi‐centre pilot randomized controlled trial testing a low‐cost, tailored, self‐help smoking cessation text message intervention for pregnant smokers (MiQuit) - Naughton, Felix (Addiction, 2017)
AIMS: To estimate the effectiveness of pregnancy smoking cessation support delivered by short message service (SMS) text message and key parameters needed to plan a definitive trial. DESIGN: Multi‐centre, parallel‐group, single‐blinded, individual randomized controlled trial. SETTING: Sixteen antenatal clinics in England. PARTICIPANTS: Four hundred and seven participants were randomized to the intervention (n = 203) or usual care (n = 204). Eligible women were < 25 weeks gestation, smoked at least one daily cigarette (> 5 pre‐pregnancy), were able to receive and understand English SMS texts and were not already using text‐based cessation support. INTERVENTION: All participants received a smoking cessation leaflet; intervention participants also received a 12‐week programme of individually tailored, automated, interactive, self‐help smoking cessation text messages (MiQuit). OUTCOME MEASUREMENTS: Seven smoking outcomes, including validated continuous abstinence from 4 weeks post‐randomization until 36 weeks gestation, design parameters for a future trial and cost‐per‐quitter. FINDINGS: Using the validated, continuous abstinence outcome, 5.4% (11 of 203) of MiQuit participants were abstinent versus 2.0% (four of 204) of usual care participants [odds ratio (OR) = 2.7, 95% confidence interval (CI) = 0.93–9.35]. The Bayes factor for this outcome was 2.23. Completeness of follow‐up at 36 weeks gestation was similar in both groups; provision of self‐report smoking data was 64% (MiQuit) and 65% (usual care) and abstinence validation rates were 56% (MiQuit) and 61% (usual care). The incremental cost‐per‐quitter was £133.53 (95% CI = –£395.78 to 843.62). CONCLUSIONS: There was some evidence, although not conclusive, that a text‐messaging programme may increase cessation rates in pregnant smokers when provided alongside routine NHS cessation care.